Characteristics of Condom and Lubricant Use among a Nationally Representative Probability Sample of Adults Ages 18–59 in the United States. (24th January 2013) - Herbenick, Debby; Schick, Vanessa; Reece, Michael; Sanders, Stephanie A.; Smith, Nicole; Dodge, Brian; Fortenberry, J. Dennis
ABSTRACT Introduction. Although most Americans have used condoms and/or lubricant during sex, little is known about the context of sexual events that involve the use of such products outside of experimentally manipulated studies. Aims. To assess, in a nationally representative study of men and women in the United States ages 18–59, the characteristics of condom and lubricant use during participants' most recent sexual event and the relationship of their condom and lubricant use to event‐level ratings of sexual quality. Methods. Data are from the National Survey of Sexual Health and Behavior, which involved the administration of an online questionnaire to a nationally representative probability sample of the U.S. adults. Main Outcome Measures. Sociodemographic items: event‐level items related to sexual behavior, condom use, lubricant use, and participants' perceptions of their arousal, pleasure, ease of erection or lubrication, and pain associated with sex. Results. During their most recent sexual experience, 27.5% of men (N = 237) and 22.3% of women (N = 175) reported using a condom. More than twice as many women as men were unsure whether the condom was lubricated (26.6% vs. 11.4%) and the material it was made of (23.6% vs. 8.9%). Participants consistently rated sex to be arousing and pleasurable whether or not they used condoms or lubricant. No significant differences were found in regard to men's ratings of the ease of their erections based on condom and lubricant use. Conclusions. Although some have concerns about how condoms or lubricants may impact their enjoyment of sex, in a nationally representative sample of men and women ages 18–59, ratings of sex were largely quite high, with few differences based on condom and lubricant use. Women, more often than men, reported being unsure about the type of condom and lubricant used, which has implications for patient education. Herbenick D, Schick V, Reece M, Sanders SA, Smith N, Dodge B, and Fortenberry JD. Characteristics of condom and lubricant use among a nationally representative probability sample of adults ages 18–59 in the United States. J Sex Med **;**:**–**.